ANALYSIS OF THE INFLUENCE OF TOTAL QUALITY MANAGEMENT IN IMPROVING PRODUCT QUALITY AT PT. KIMIKA USAHA PRIMA - Priatmaja, Cantika Rahmadhantri; Hafidzi, Achmad Hasan; Wibowo, Yohanes Gunawan (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of implementing Total Quality Management (TQM) on product quality improvement at PT. Kimika Usaha Prima. The study focuses on three key TQM indicators: customer focus, teamwork, and education and training. Employing a quantitative approach, the research involved 35 respondents selected using a saturated sampling technique. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression to determine the relationships among the variables. The findings reveal that the three TQM indicators customer focus, teamwork, and education and training have a significant influence on product quality improvement. These results suggest that an effective application of TQM principles can enhance the quality of products produced by the company. This study provides practical recommendations for PT. Kimika Usaha Prima to strengthen its competitive advantage through the structured and sustainable implementation of TQM strategies. Moreover, it highlights the importance of organizational commitment to prioritizing customer satisfaction, fostering teamwork, and investing in human resource development as key drivers of quality enhancement.